2009
DOI: 10.1002/adsc.200900144
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Phenol in Supercritical Carbon Dioxide Catalyzed by Palladium Supported on Al‐MCM‐41: A Facile Route for One‐Pot Cyclohexanone Formation

Abstract: The hydrogenation of phenol has been carried out in supercritical carbon dioxide (scCO 2 ) under very mild reaction conditions at the temperature of 50 8C over palladium supported Al-MCM-41 (metal loading~1%). This palladium catalyst is shown to be highly active and promotes the selective formation of cyclohexanone (~98%), an industrially important compound, in a "one-pot" way. The effects of different variables like carbon dioxide and hydrogen pressure, reaction time and also silica/alumina ratio of the MCM-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 60 publications
1
80
0
2
Order By: Relevance
“…It is reported by Chatterjee et al that phenol is hydrogenated to cyclohexanone with a high selectivity > 97% with Pd/Al-MCM-41 catalyst at H 2 and CO 2 pressures of 4 MPa and 12 MPa, respectively [24]. The selectivity to cyclohexanone was found to depend on CO 2 pressure and it was < 60% at 7 MPa or below.…”
Section: Figure 17mentioning
confidence: 96%
See 2 more Smart Citations
“…It is reported by Chatterjee et al that phenol is hydrogenated to cyclohexanone with a high selectivity > 97% with Pd/Al-MCM-41 catalyst at H 2 and CO 2 pressures of 4 MPa and 12 MPa, respectively [24]. The selectivity to cyclohexanone was found to depend on CO 2 pressure and it was < 60% at 7 MPa or below.…”
Section: Figure 17mentioning
confidence: 96%
“…The Lewis acidity of the MCM-41 supports of Chatterjee's catalysts [24] may contribute to their high selectivity to cyclohexanone observed.…”
Section: Figure 17mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a probable mechanism for the hydrogenation of phenols on Pd-based catalysts indicated that phenols were adsorbed and activated on the support [37], while H 2 was activated on the Pd and induced the hydrogenation of adsorbed phenols. If the adsorption of phenols occurred through the hydroxyl, the methoxy group in ortho-position may have increased steric hindrance of the reaction such that guaiacol had more trouble being hydrogenated than the other phenols did [19,37]. following.…”
Section: Hydrogenation Of Other Substituted Phenolsmentioning
confidence: 99%
“…Additionally, high temperatures require more energy consumption and thus an increase in cost. Recently, much attention has been focused on the liquid phase hydrogenation of phenols [8,[17][18][19][20][21][22][23][24][25]. For example, Huang et al [26] prepared a high-performance PdRu bimetallic catalyst on mesoporous silica nanoparticles for the hydrogenation of phenol in CH 2 Cl 2 solvent.…”
Section: Introductionmentioning
confidence: 99%